Incidence of diabetes mellitus in thai women with polycystic ovary syndrome - S. Leelaphiwat (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Objective: To determine the incidence and risk factors of type 2 diabetes mellitus (T2DM) in Thai women with Polycystic Ovary Syndrome (PCOS). Materials and Methods: A retrospective cohort study in PCOS women diagnosed according to the Rotterdam Criteria was conducted. All PCOS women registered who had no T2DM at the visit were recruited in the present study. According to the protocol, these women were assigned to have a 75 g oral glucose tolerance test done every two years unless T2DM was found. Results: One hundred fourteen PCOS women were included in the present study. Age, body mass index, and waist circumference were 27.4±5.4 years, 24.8±6.1 kg/m2, and 77.7±16.2 cm, respectively. In the normal glucose tolerance (NGT) group (n=82), the incidence of T2DM was 1.2% (1 out of 82) and 3.1% (2 out of 64) at 2- and 4-year follow-up. Women with NGT converted to non- DM abnormal glucose tolerance (AGT) in 18.3% and 15.6% at 2- and 4-year follow-up. In the non-DM AGT group, the incidence rates of T2DM were 18.8% (6 out of 32) and 21.7% (5 out of 23) at 2- and 4-year follow-up. Obesity and non-DM AGT were the important risk factors for developing T2DM with OR of 4.2 (95% CI 1.2 to 14.6) and 8.9 (95% CI 2.5 to 31.0), respectively Conclusion: The current retrospective cohort study determined the overall incidence of T2DM was 12.3% (14 out of 114) of 4-year follow-up. Non-DM AGT and obesity were the important risk factors for conversion to T2DM.